Cultivo heterotrófico de Aphanothece microscopica Nägeli e Chlorella vulgaris em diferentes fontes de carbono e em vinhaça - Bonini, Monica de Albuquerque (2012)
ABSTRACT Microalgae include both algae Chlorophycea and cyanobacteria. These organisms have attracted interest due to its versatile metabolism, since some strains have, additionaly to photosynthetic metabolism, hability to grow in the dark by the consumption of simple organic molecules, such as glucose, acetate and glycerol. This hability suggests the application of these microorganisms in several areas, such as biological treatment of agroindustrial wastewater, aiming the removal of nutrients and organic matter. São Paulo/Brazil is one of the main producers of ethanol from sugarcane, generating a considerable amount of vinasse. Vinasse represents the main wastewater from de sugarcane agroindustry, being usually applied as fertigation in sugarcane crops. In this context, this study aimed to evaluate the heterotrophic growth of cyanobacterium Aphanothece microscopica Nägeli and the chlorophyceae Chorella vulgaris in synthetic culture media supplemented with organic carbon source and in vinasse, aiming to produce biomass and application it in wastewater treatment. Mixotrophic cultures were conducted to select the optimal concentration of organic substrate for the growth of microalgae, which were evaluated in heterotrophic cultures. Additionally, experiments have been conducted with pre-treated vinasse, evaluating the COD removal and the glucose and potassium incorporation. By the mixotrophic tests was selected the optimal concentrations of 25 and 12.5 g.L-1 glucose, 0.5 and 1.25 g.L-1 potassium acetate and 0.46 and 0.92 g.L-1 glycerol as ideal for the cultivation of Aphanothece microscopica Nägeli and Chlorella vulgaris, respectively, which reflected on the maximum specific growth rate between 0.0072 and 0.043 h-1. In the heterotrophic cultures the maximum specific growth rate was greater or equal to both microalgae in all carbon sources, with reduction between 30.4 and 90% of the initial concentrations of substrates. The experiments demonstrated possibility to use vinasse as culture media for both microalgae, especially Aphanothece microscopica Nägeli. In this conditions, results indicated the maximum removals of glucose (55.5%), COD (60.8%) and potassium (13%) by the cianobacterium, and 83.7% of glucose, 25% of COD and 13.8% of potassium by Chlorella vulgaris. The results suggest the heterotrophic metabolism for both microorganisms, pointing an interesting alternative to use of wastewater as culture media to produce high-value biomass from a low-cost way.